Effect of Drying Temperature on Drying Characteristics, Total Phenolic Content and Antioxidant Activity of Slightly Sticky Mango (Mangifera Indica L.) Sheet - S Nungwongsa; S Sayasoonthorn; D Jaisut; T Chungcharoen; W Thakhiew; R Thuwapanichayanan (My University, 2021)
Abstract Dried slightly sticky mango sheets is healthy sweet snack, having slightly chewy texture. The objective of this work was to study the effect of drying temperatures (60, 70 and 80 °C) on the drying characteristics, total phenolic content (TPC), antioxidant activity (assessed by DPPH and ABTS scavenging activity assays) and specific energy consumption of the dried slightly sticky mango sheets. The experimental results showed that the times required to reach the desired final moisture content were 230, 150 and 120 min when drying was performed at the temperatures of 60, 70 and 80 °C, respectively. The total specific energy consumption (SECtotal) values of the drying at 70 and 80 °C were lower than that at 60 °C. However, the TPC and the antioxidant activities assessed by DPPH and ABTS scavenging activity assays were not significantly different amongst the samples dried at different temperatures.
Keywords: Mangifera; ABTS; Phytochemicals and Antioxidant Activities